System biology-guided chemical proteomics to discover protein targets of monoethylhexyl phthalate in regulating cell cycle - Xu, Tengfei (2022)
Chemical proteomics methods have been used as effective tools to identify novel protein targets for small molecules. These methods have great potential to be applied as environmental toxicants to figure out their mode of action. However, these assays usually generate dozens of possible targets, making it challenging to validate the most important one. In this study, we have integrated the cellular thermal shift assay (CETSA), quantitative proteomics, metabolomics, computer-assisted docking, and target validation methods to uncover the protein targets of monoethylhexyl phthalate (MEHP). Using the mass spectrometry implementation of CETSA (MS-CETSA), we have identified 74 possible protein targets of MEHP. The Gene Ontology (GO) enrichment integration was further conducted for the target proteins, the cellular dysregulated proteins, and the metabolites, showing that cell cycle dysregulation could be one primary change due to the MEHP-induced toxicity. Flow cytometry analysis confirmed that hepatocytes were arrested at the G1 stage due to the treatment with MEHP. Subsequently, the potential protein targets were ranked by their binding energy calculated from the computer-assisted docking with MEHP. In summary, we have demonstrated the development of interactomics workflow to simplify the redundant information from multiomics data and identified novel cell cycle regulatory protein targets (CPEB4, ANAPC5, and SPOUT1) for MEHP.